2006
DOI: 10.1289/ehp.8451
|View full text |Cite
|
Sign up to set email alerts
|

The Estrogenic Effect of Bisphenol A Disrupts Pancreatic β-Cell Function In Vivo and Induces Insulin Resistance

Abstract: The function of the pancreatic β-cell is the storage and release of insulin, the main hormone involved in blood glucose homeostasis. The results in this article show that the widespread environmental contaminant bisphenol-A (BPA) imitates 17β-estradiol (E2) effects in vivo on blood glucose homeostasis through genomic and nongenomic pathways. The exposure of adult mice to a single low dose (10 μg/kg) of either E2 or BPA induces a rapid decrease in glycemia that correlates with a rise of plasma insulin. Longer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
395
3
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(431 citation statements)
references
References 55 publications
24
395
3
9
Order By: Relevance
“…Therefore, it is reasonable to suggest that BPA, similarly to E2, binds to ERa and produces changes in these rapid signals. Few data address the ability of BPA to mediate nongenomic estrogenic actions (see [25][26][27][28][29][30][31] and, as far we know, no information focuses on the involvement of these pathways in the proliferative effect of BPA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to suggest that BPA, similarly to E2, binds to ERa and produces changes in these rapid signals. Few data address the ability of BPA to mediate nongenomic estrogenic actions (see [25][26][27][28][29][30][31] and, as far we know, no information focuses on the involvement of these pathways in the proliferative effect of BPA.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological levels of estrogen are involved in maintaining normal insulin sensitivity, but an excess of estrogen, such as exposure to chemicals with estrogenic activity at an inappropriate concentration, would increase the risk of developing insulin resistance and diabetes (Zhang et al 2002, Margolis et al 2004, Godsland 2005. One of the most striking examples is that adult male mice injected with a daily dose of 100 mg/kg per day bisphenol A (BPA) or 17b-estradiol (E 2 ) for 4 days showed higher insulin secretion, thereby resulting in insulin resistance and postprandial hyperinsulinemia (Alonso-Magdalena et al 2006). Our previous studies also have demonstrated that perinatal exposure to 50 mg/kg per day BPA led to severe glucose and insulin intolerance in adult rat offspring along with progressive damage of b-cells .…”
Section: Introductionmentioning
confidence: 99%
“…The potencies of these compounds in nuclear transcription reporter assays range from very weak (dieldrin, DDE, endosulfan), to somewhat weak (bisphenol A and nonylphenol), to quite strong (DES and coumestrol). There is a paucity of data on the ability of environmental estrogens to mediate nongenomic effects at low concentrations [18][19][20][21][22][23][24]. Most published studies examine only very high (μM-mM) concentrations (for example, [25]) in the range required to see any effects on nuclear transcription responses, but which are rarely reached at contamination sites.…”
Section: Introduction Xenoestrogens and Their Known Modes Of Actionmentioning
confidence: 99%